2017
DOI: 10.1186/s12944-017-0439-0
|View full text |Cite
|
Sign up to set email alerts
|

Effects of simvastatin on serum adiponectin: a meta-analysis of randomized controlled trials

Abstract: BackgroundEffects of simvastatin on serum level of adiponectin, a protein conferring benefits in both cardiovascular and metabolic system, are not fully determined.MethodsA meta-analysis of randomized controlled trials (RCTs) was performed. Studies were identified by searching of Pubmed, Embase, and the Cochrane Library databases. Heterogeneity among the RCTs was determined by Cochrane’s Q test and I2 statistics. Meta-analysis was performed with random-effect model or fixed-effect model according to the hetero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 35 publications
(38 reference statements)
0
5
0
Order By: Relevance
“…Adiponectin increases insulin sensitivity [117], an effect also observed after weight loss and the consequent increase in plasma levels [118]. Simvastatin treatment, often observed in patients with CVD, increases adiponectin levels over 12 weeks but not below 8 weeks [119].…”
Section: Adiponectinmentioning
confidence: 96%
“…Adiponectin increases insulin sensitivity [117], an effect also observed after weight loss and the consequent increase in plasma levels [118]. Simvastatin treatment, often observed in patients with CVD, increases adiponectin levels over 12 weeks but not below 8 weeks [119].…”
Section: Adiponectinmentioning
confidence: 96%
“…A meta-analysis of 12 RCTs with 16 comparisons and 1042 patients showed that serum adiponectin was not significantly affected by simvastatin (WMD: 0.42 μg/mL; 95% CI, −0.66 to 1.50 μg/mL) [ 180 ]. In a systematic review and meta-analysis of 43 studies, a significant increase in plasma adiponectin levels was observed after statin therapy (WMD: 0.57 μg/mL, 95% CI: 0.18 to 0.95, p = 0.004) [ 181 ].…”
Section: How Can We Increase Adiponectin?mentioning
confidence: 99%
“…One is to increase levels of adiponectin, such as injection of adiponectin and increase of adiponectin expression via compounds. The second is to activate AdipoRs, including small molecule and peptide agonist activating AdipoRs or increase levels of AdipoRs metformin and liraglutide and Exenatide, [134][135][136][137][138] and hypolipidemia drugs, such as statin, ezetimibe and fibrate, [139][140][141] have all been shown to increase adiponectin concentrations in the plasma.…”
Section: Known Strategies To Increase Adiponectin Actionmentioning
confidence: 99%
“…Furthermore, some compounds are used to increase adiponectin expression. PPARγ agonist drugs, such as troglitazone, pioglitazone, rosiglitazone and MK‐0767, 98,130–133 anti‐diabetic drugs, such as dipeptidyl peptidase‐4 inhibitors (DPP4i), α‐Glycosidase inhibitors, metformin and liraglutide and Exenatide, 134–138 and hypolipidemia drugs, such as statin, ezetimibe and fibrate, 139–141 have all been shown to increase adiponectin concentrations in the plasma.…”
Section: Therapeutic Strategies To Increase Adiponectin Action and Its Application In Aquaculturementioning
confidence: 99%